PENGARUH AKTIVASI ADSORBEN BIJI PEPAYA TERHADAP ADSORPSIION LOGAM BESI (Fe) DAN TEMBAGA (Cu) DALAM AIR LIMBAH - Anita Karunia Zustriani (Integrated Lab Journal, 2019)
Research on heavy metals (iron and copper) ions uptake in wastewater using papaya seed powder has been conducted. The purpose of this study was to provide solutions on handling and processing of heavy metal waste in the laboratory. The adsorption method is used for this purpose. Activation of the adsorbent was carried out to determine the effectiveness of the unactivated and activated adsorbents.Activation is done using a neutral activator (aquadest). Papaya seed as the adsorbent agent (both un-activated and activated ones) was used in four mass variations in order to determine the optimum mass of papaya seed powder to absorb the heavy metals. The results show that the optimum adsorbent mass was 2 grams for both metal ions (iron and copper). The activated adsorbent is more effective in the adsorption process. The adsorption efficiency of iron (Fe) metal ions in wastewater was 58.80%, the adsorption capacity value was 257.10 mg/g. While the adsorption efficiency of copper (Cu) metal ions in wastewater was 90.70%, the adsorption capacity value was 345.04mg/g.